Panicum maximum Jacq. cv. Mombaza resistance to ametrine herbicide, Costa Rica - Quesada Cabezas, Osvaldo David (2026)
Chemical weed control remains a widely used tool in agricultural and livestock production systems. However, intensive use and, in some cases, inadequate herbicide management has led to the emergence of weed populations with reduced sensitivity to these products. In Costa Rica, cases of herbicide resistance have been recorded, but none involving P. maximum. This study evaluated the response of Panicum maximum Jacq. cv. Mombaza biotypes to the ametrine herbicide under greenhouse conditions, to determine possible resistance at the field level. Between February and December 2023, an experiment was conducted in Tambor, Alajuela, to analyze the response of P. maximum biotypes to ametryn and to determine the resistance index (RI). The biotypes were obtained from livestock farms and pineapple plantations in various areas of Alajuela. The plants were treated with increasing doses of herbicide, and visual damage and fresh weight were assessed 14 days after application (DAA) to calculate the ED50 and RI values. A biotype of P. maximum resistant to ametrine was identified, requiring twice or more the amount of herbicide to achieve a 50% reduction in fresh weight compared to the most sensitive biotype. Continued use of herbicides such as ametryn in the field could favor the selection and spread of less sensitive plant populations, further worsening the resistance problem.